Building Scalable and Robust Adaptive Capacity Arbitration Algorithms for the Next Generation of WCDMA Wireless Networks - Dallal, Haroon Rashid Hammood Al (Journal La Multiapp, 2025)
The plans to improve execution in optical multi-transporter Code Division Different Access (CDMA) upstream correspondence frameworks. The review centers around defeating difficulties connected with further developing correspondence effectiveness, diminishing obstruction, and expanding generally speaking throughput in optical multi-transporter CDMA organizations. Through the examination of various coding systems and improvement strategies, this exploration adds to the progression of optical correspondence advancements.